The Role of Tenas Effendy in The Development of Malay Culture in Riau Province (1952-2015) - Arifin, M. Nur; Ahmal, Ahmal; Fikri, Asyrul (Journal of Educational Sciences, 2025)
This research examines the role of Tenas Effendy in the development of Malay culture in Riau Province from 1952 to 2015. The background of the study highlights the current era, where globalization has led to the erosion of cultural heritage. Culture is a legacy from the ancestors of a community. The development, preservation, and sustainability of Malay culture in Riau are closely linked to the contributions of Malay cultural figures, particularly Tenas Effendy. The objectives of this research are: (1) To understand the life history of Tenas Effendy; (2) To explore his role in the development of Malay culture in Riau; and (3) To examine the implementation of his role in the present-day development of Malay culture in Riau. The research employs a historical method. The findings reveal Tenas Effendy's significant contributions to the development of Malay culture in Riau, especially in preserving the original culture of the Petalangan tribe and the Malay teachings. It can be concluded that Tenas Effendy plays an important role in the development of Malay culture in Riau Province.